2014
DOI: 10.29043/liminar.v12i2.340
|View full text |Cite
|
Sign up to set email alerts
|

La mortalidad materna y los nudos en la prestación de los servicios de salud en Chiapas. Un análisis desde la interculturalidad

Abstract: La mortaLidad materna y Los nudos en

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 5 publications
1
5
0
1
Order By: Relevance
“…In the communities studied, women prefer midwifery care because of the social and cultural proximity amid a context with low state presence and poor quality of health services. This agrees with other authors, who have identified that cultural and geographic proximity mediates women’s choice of where and how their children are born [ 18 , 28 , 29 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the communities studied, women prefer midwifery care because of the social and cultural proximity amid a context with low state presence and poor quality of health services. This agrees with other authors, who have identified that cultural and geographic proximity mediates women’s choice of where and how their children are born [ 18 , 28 , 29 ].…”
Section: Discussionsupporting
confidence: 92%
“…This is associated with the poor presence of institutions in those areas and the low accessibility of health services for women who live far from urban centers. Moreover, afro-descendant and indigenous women have experienced inequalities in the health system because it is anchored to a mestizo society that does not know the local language, cultural practices and beliefs [ 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Like for the rest of the world, this was the indicator exhibiting the highest degree of inequality across social groups and regions of the country. Even though maternal deaths on average had decreased consistently in the previous decade, major efforts were still needed in the poorest areas of the southern states of Mexico, where geographic, organizational, financial, and cultural barriers limited women’s access to maternal health care [31]. The differences among states were huge.…”
Section: Discussionmentioning
confidence: 99%
“…Por tales situaciones, reflejadas en la pobreza en el acceso a la salud y la inexistencia de tratamientos, la inclemencia y el tiempo del padecimiento de enfermedades es mayor entre la población indígena (Del Álamo, 2006) y, por ende, tienen mayor riesgo de morir en procedimientos como el parto para el caso de mujeres, además tienen menor cobertura en salud y usan menos la atención ambulatoria y hospitalaria (Freyermuth, 2014; Comisión Nacional para el Desarrollo de Pueblos Indígenas-Programa de las Naciones Unidas para el Desarrollo, 2010; Leyva et al, 2013). En lo anterior intervienen aspectos culturales para la prestación y la recepción de la atención hospitalaria (Gómez et al, 2017), que se convierten en barreras de disponibilidad, accesibilidad y aceptabilidad en la atención médica en contextos indígenas (Loyola et al, 2016).…”
Section: Marco Teóricounclassified